Groundwater resource evaluation of the Kathmandu valley - Gautam, Ramesh; Rao, G. Krishna (Journal of Nepal Geological Society, 1991)
This article briefly deals with the nature of the aquifers and total groundwater reserves of the Kathmandu Valley. It is attempted ·to evaluate and estimate the total groundwater resources in the Valley. Based on the present condition it is suggested to prevent over exploitation situation of groundwater resource and to increase the perennial yield through artificial methods of groundwater recharge.